Ramifications of reproductive diseases on the recovery of the Sumatran Rhinoceros Dicerorhinus sumatrensis (Mammalia: Perissodactyla: Rhinocerotidae) - Nan E. Schaffer (Journal of Threatened Taxa, 2020)
The Sumatran Rhinoceros Dicerorhinus sumatrensis is on the edge of extinction.  The decline of this species was initially attributed to poaching and habitat loss, but evidence presented here indicates that reproductive failure has also been a significant cause of loss, and continues to affect wild populations.  Indonesia’s remaining populations of Sumatran Rhino are small and scattered, with limited access to breeding opportunities with unrelated mates.  This leaves them subject to inbreeding and isolation-induced infertility, linked to fertility problems analyzed here.  Sumatran Rhino females in captivity showed high rates (>70%) of reproductive pathology and/or problems with conception, which has significantly hindered the breeding program.  Technological advances enabling examination immediately after capture revealed similarly high rates and types of reproductive problems in individuals from wild populations.  The last seven Sumatran Rhino females captured were from areas with small declining populations, and six had reproductive problems.  Going forward, capturing similarly compromised animals will take up valuable space and resources needed for fertile animals.  The high risk of infertility and difficulty of treating underlying conditions, coupled with the decreasing number of remaining animals, means that the success of efforts to build a viable captive population will depend upon utilizing fertile animals and applying assisted reproductive techniques.  Decades of exhaustive in situ surveys have not provided information relevant to population management or to ascertaining the fertility status of individual animals.  Thus the first priority should be the capture of individuals as new founders from areas with the highest likelihood of containing fertile rhinos, indicated by recent camera trap photos of mothers with offspring.  In Sumatra these areas include Way Kambas and parts of the Leuser ecosystem.